2014
DOI: 10.1051/0004-6361/201323101
|View full text |Cite
|
Sign up to set email alerts
|

The Na-O anticorrelation in horizontal branch stars

Abstract: We obtained high-resolution spectra for 94 candidate stars belonging to the HB of M 22 with FLAMES. Previous works have indicated that this cluster has split subgiant (SGB) and red giant branches (RGB) and hosts two different stellar populations, differing in overall metal abundance and both exhibiting a Na-O anti-correlation. The HB stars we observed span a restricted temperature range (7800 < T eff < 11 000 K), where about 60% of the HB stars of M 22 are. Within our sample, we can distinguish three groups of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 72 publications
4
36
0
Order By: Relevance
“…Recently, Na-O anticorrelation is also discovered in HB stars for many GCs (Gratton et al 2013(Gratton et al , 2014. Marino et al (2014) analyzed nearly 100 HB stars with different temperatures in NGC 2808 and confirmed that some blue HB stars in this GC present higher helium abundance than primordial content by △Y = 0.09 ± 0.01.…”
Section: Introductionmentioning
confidence: 79%
“…Recently, Na-O anticorrelation is also discovered in HB stars for many GCs (Gratton et al 2013(Gratton et al , 2014. Marino et al (2014) analyzed nearly 100 HB stars with different temperatures in NGC 2808 and confirmed that some blue HB stars in this GC present higher helium abundance than primordial content by △Y = 0.09 ± 0.01.…”
Section: Introductionmentioning
confidence: 79%
“…It would be very interesting to point out the recent result by Gratton et al (2014). They carried out the spectroscopic survey of the BHB stars in M22 and found a significant fraction (≈ 18%) of the metal-rich helium-enhanced BHB stars in their sample (Group 3 designated by Gratton et al).…”
Section: Horizontal Branch Starsmentioning
confidence: 91%
“…D' Antona et al 2002;Milone et al 2014) and there also exist direct spectroscopic observational evidences of helium enhancement in GC HB stars (Marino et al 2014a;Gratton et al 2014). …”
Section: Horizontal Branch Starsmentioning
confidence: 97%
See 2 more Smart Citations